Optical Properties of Oxidized, Hydrogenated, and Native Zirconium Surfaces for Wavelengths from 0.3 to 25 µm − A Study by Ex Situ and In Situ Spectroscopic Ellipsometry. Issue 8 (15th February 2019) - Petrik, Peter; Romanenko, Alekszej; Kalas, Benjamin; Péter, László; Novotny, Tamás; Perez‐Feró, Erzsébet; Fodor, Bálint; Agocs, Emil; Lohner, Tivadar; Kurunczi, Sándor; Stoica, Mihai; Gartner, Mariuca; et al.
Abstract : To characterize zirconium surfaces in forms of tubes and plates for nuclear applications, ellipsometry has been used. It has been shown earlier that ellipsometry can be used even on the surface of tubes with a diameter of 9.1 mm, when applying proper focusing. Reference refractive indices have also been determined for both zirconium and zirconium oxide, and demonstrated the capability of ellipsometry for the determination of the thickness and refractive index of the surface oxide applying different oxidation parameters. In this study, processed zirconium surfaces using the technique developed in author's previous work is characterized. Both ultra violet‐visible‐near infrared and mid‐infrared ellipsometry to study the thicknesses of the surface layers as well as the dielectric functions of both the layers and the substrate are used. A heat cell that allows multiple angle of incidence ellipsometry measurement at elevated temperatures is also developed. This setup is used to monitor the temporal behavior of hydrogenated and oxidized zirconium surfaces. Abstract : Ellipsometry is used for the in situ characterization of zirconium surfaces in forms of tubes and plates for nuclear applications, using a special cell for annealing. The capability of ellipsometry is demonstrated for the determination of the thickness and reference refractive indices of both zirconium and zirconium‐oxide in a wide spectral range.